Pengaruh Aplikasi GeoGebra dalam Meningkatkan Kemampuan Berpikir Kritis Siswa di SMPN Cibinong - Rezkiyana Hikmah (Universitas Indraprasta PGRI Jakarta, 2020)
The development of GeoGebra media is a form of a technological contribution to the field of education, especially mathematics. The use of GeoGebra media in this study is related to making lines in an equation to find gradients. This study aims to see whether the critical thinking skills of students who learn with GeoGebra media are better than ordinary learning and whether the increase in critical thinking skills of students with GeoGebra media is better than ordinary learning. The sample of this study was class VIII in the School Year 2019/2020 at SMPN 1 Cibinong. The samples were 60 students. This type of research is a quasi-experimental research design with a non-equivalent control group. The instrument used were pretest and postest to see n-gain critical thinking skills. The research data were analyzed with the Mann-Whitney test. The result was the improvement of the critical thinking ability of students who learn with GeoGebra media better than students who learn with ordinary learning.